الموارد المالية في ظل المتغيرات التشريعية دراسة تطبيقية ولاية النيل الأبيض للفترة من العام 1994م – 2012م - د. صلاح محمد إبراهيم (White Nile Journal for Studies and Research, 2014)
The aim of this study is to investigate the financial resources under the legislation which passed on the regime in Sudan during the historical periods for the period (19942012-) and the legislation according to levels of government and the laws of the apportionment of financial resources and the distribution of wealth and limited financial resources at the federal state and local conflicts and try each level hegemony and grip on large financial resources And passage of legislation that gives the center (federal) distribution right and a one the largest proportion of the financial resources and national domination and control over the state and stripped of the proceeds of national projects and conversion rate them to the U.S. current transfers and compensation for agricultural) without standards fair but stop dividing resources on favoritism and influence and the relationship of the state Center. (